2008
DOI: 10.1177/0093854808320169
|View full text |Cite
|
Sign up to set email alerts
|

Offender Coercion in Treatment

Abstract: Mandating offenders to attend correctional treatment is a controversial function of the justice system, in part because of the uncertainty about the effectiveness of such practice. A meta-analysis was conducted to compare the effectiveness of mandated, coerced, and voluntary correctional treatment in reducing recidivism. A search of correctional treatment studies resulted in 129 studies meeting the inclusion criteria. In general, mandated treatment was found to be ineffective in several analyses, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(41 citation statements)
references
References 145 publications
3
37
1
Order By: Relevance
“…Similar to past meta-analysis on criminal justice intervention, the present results demonstrate the effectiveness of community interventions (Parhar et al, 2008). The range of odds ratios found in the present study is similar to that of other community studies (57% Lowenkamp, Hubbard, Makarios, & Latessa, 2009;61%, Hollin et al, 2008;33-68%, Palmer et al, 2007).…”
Section: Group Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to past meta-analysis on criminal justice intervention, the present results demonstrate the effectiveness of community interventions (Parhar et al, 2008). The range of odds ratios found in the present study is similar to that of other community studies (57% Lowenkamp, Hubbard, Makarios, & Latessa, 2009;61%, Hollin et al, 2008;33-68%, Palmer et al, 2007).…”
Section: Group Resultssupporting
confidence: 90%
“…Related to therapeutic relationship is the amount of coercion used to have clients participate in an intervention program. The less mandatedness and coercion are used in a program, in conjunction with greater client choices, the greater are the reductions in negative outcomes (Parhar, Wormith, Derkzen, & Beauregard, 2008). Overall, the application of appropriate content and processes to criminal justice interventions results in substantial reductions in negative outcomes.…”
mentioning
confidence: 99%
“…This is consistent with earlier research (Bonta et al, 1998). It may be explained by the element of coercion into treatment; individuals who enter treatment voluntarily have been shown to be less likely to re-offend than those mandated or coerced to do so (Parhar et al, 2008). In this context, it may be relevant that our other main fi nding was that the greater degree the clients perceived their need for mentalhealth services, the less likely they were to be arrested subsequently.…”
Section: Discussionsupporting
confidence: 88%
“…International literature has pointed to different treatment perspectives on several treatment-related issues (e.g. Barlow & Wolfsen, 1997;Clearly & Warren, 1998;Menger, 2008;Mezey, Hassell, & Bartlett, 2005, Parhar, Wormith, Derkzen, & Beauregard, 2008. More specific, in Belgium, the study of Boers et al (2011) also revealed different opinions on various treatment-related issues.…”
Section: Introductionmentioning
confidence: 99%
“…Another debate within this controversy is whether a minimal motivation of the MIO to change is necessary to achieve an effective treatment. According to Parhar et al (2008), complete ignorance of the offender's motivation for treatment may equate to coercion into treatment, which may not lead to the best treatment outcomes, particularly when treatment is located in custodial settings. In this respect, the issue emerges whether to view an individual's motivation for treatment as a selection criterion, i.e.…”
mentioning
confidence: 99%